The Next 4 Billion : Characterizing BoP Markets - Hammond, Allen L.; Kramer, William J.; Katz, Robert S.; Tran, Julia T.; Walker, Courtland (World Bank, Washington, DC, 2012)
This study uses empirical measures to describe the behavior of low-income populations as consumers and producers. In aggregate, their purchasing power suggests significant market opportunities. By quantifying this market and describing its characteristics, the author hopes to stimulate business development and investment that can better meet the needs of these populations, as well as increase their productivity and incomes and empower their entry into the formal economy. The four billion people at the base of the economic pyramid Balance of Payment (BoP) all those with incomes below $3,000 in local purchasing power live in relative poverty. Their incomes in current U.S. dollars are less than $3.35 a day in Brazil, $2.11 in China, $1.89 in Ghana, and $1.56 in India. Yet together they have substantial purchasing power: the BoP constitutes a $5 trillion global consumer market.